Contribution factors to the success of book printers in surviving book printing industry / Shalida Mohd Rosnan - Mohd Rosnan, Shalida (2016)
The increase in popularity of digital media technology has led to a tremendous swing towards the digital distribution of content over traditional printing processes. The new technology and challenges in book printing business changed the industry landscape. These challenges lead to the significant questions about on how printers may survive in the book printing industry. However, the discussion that focuses on factors to be implemented to success in surviving the challenges is scarce. The purpose of this research was to identify the factors that led to the success of book printers in Selangor and Kuala Lumpur. Through a case study of five printers, Ultimate Print Sdn Bhd, BS Print Sdn Bhd, Times Offset (Malaysia) Sdn Bhd, Naga Global Print Sdn Bhd and Harian Zulfadzli Sdn Bhd, this paper investigates on what factors strategically implemented to thrive and survive in the business. The researcher conducted openended interviews among book printers and identified factors to sustain the business. The researcher obtained the data by analysing the qualitative data from interviews and documents. Results from this research suggested that to remain in the book printing industry; printers must have these factors; investing in new technologies, improving efficiency, focusing on marketing to expand business and working closely with customers.